Bleeder: A Memoir - Shelby Smoak (Michigan State University Press, 2013)
In 1974 when I was two, an unusually large bruise developed across my back and refused to heal. My parents were confused. How can this be? This bruise isn’t normal? What is wrong with our son? Necessarily, their concern carried them (and me) to the emergency room— a site that will become commonplace to me as I age. Three days later, a test returned positive for hemophilia and my problem was solved. I was treated with a plasma product; the bruise healed; but I went home a hemophiliac, a free- bleeder. And my life changed forever.